Strategi Venezuela Menyepakati ALBA Dalam Menghadapi Ekspansi Perdagangan Amerika Serikat Dikawasan Amerika Latin - Wahyu, Septian; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In 2004 Venezuela and Cuba have agreed on a regional collaboration in latin america called Alternative Bolivarian Para las Americas an abbreviated ALBA. This collaboration is formed as a resistance facing U.S. trade expansion to bring a mission neoliberalism. With the formation of ALBA, Venezuela is the regional co-operation leaders make strategic measures to face Neoliberalism. In 2010 ALBA has had a total of 10 member countries. As counter hegemony, ALBA also worked in three space. In the space of ideas, countries member need complementary principles solidarity and cooperation to achieve prosperity and equitable regional development. At the institutional space, the idea is then integrated into ALBA.Key words: Regionalism, ALBA, Trade Expansion, Strategy Integration